2022
DOI: 10.1002/stco.202200003
|View full text |Cite
|
Sign up to set email alerts
|

High‐cycle variable amplitude fatigue experiments and design framework for bridge welds with high‐frequency mechanical impact treatment

Abstract: Fatigue enhancement by way of high-frequency mechanical impact (HFMI) treatment can enable effective design and construction of steel bridges. However, bridges may experience high and varying mean stresses, the effects of which are not covered today by any design recommendation or in the literature on HFMI-treated joints. In this study, fatigue experiments were conducted with realistic in-service bridge loading, which revealed the same high fatigue performance as for constant amplitude loading. The effect of m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
18
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(18 citation statements)
references
References 30 publications
0
18
0
Order By: Relevance
“…More fatigue tests were conducted under high-stress ratios (0.5 ≤ R ≤ 0.8) in [8], and the results supported the trend of the IIW method in terms of reducing the fatigue strength class depending on the R-ratio. In principle, the trend follows a decrease in one fatigue strength class per 0.12 increase in the R-ratio [12,13], as can be seen in Figure 1. In a design situation, the R-ratios from traffic loads are unknown to designers.…”
Section: Introductionmentioning
confidence: 88%
See 4 more Smart Citations
“…More fatigue tests were conducted under high-stress ratios (0.5 ≤ R ≤ 0.8) in [8], and the results supported the trend of the IIW method in terms of reducing the fatigue strength class depending on the R-ratio. In principle, the trend follows a decrease in one fatigue strength class per 0.12 increase in the R-ratio [12,13], as can be seen in Figure 1. In a design situation, the R-ratios from traffic loads are unknown to designers.…”
Section: Introductionmentioning
confidence: 88%
“…If not, a correction method can be used to account for the mean stress effect from traffic loads in design. The authors have, in a previous publication [12], suggested such a method to consider the mean stress effect in the design of HFMI-treated road bridges. This method considers the mean stress effects produced by the combined effects of self-weight and traffic load based on the collective mean stresses produced by measured traffic data.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations